Uniform fantasies : soldiers, sex, and queer emancipation in imperial Germany - Schneider, Jeffrey (Lecturer in German studies) (German and European studies, 2023)
"Starting in the nineteenth century in Germany, colourful military uniforms became a locus for various queer male fantasies, fostering an underground sexual economy of male prostitution as well as a political project to exploit the army's prestige for queer emancipation. In the first decade of the twentieth century, however, a series of scandals derailed this emancipatory project. Simultaneously, public debates began to invoke homosexuality, sadism, transvestism, and other sexological concepts to criticize military policies and practices. In pursuing the threads with which queer authors and activists stitched their fantasies about uniforms, Jeffrey Schneider offers fresh perspectives on key debates over military secrecy, disciplinary abuses in the army, and German militarism. Drawing on a vast trove of materials ranging from sexological case studies, trial transcripts, and parliamentary debates to queer activist tracts, autobiographies, and literary texts, Uniform Fantasies uncovers a particularly modern set of concerns about such topics as outing closeted homosexuals, the presence of gays in the military, and whether men in uniform are more masculine or more insecure about their sexual identity."--